Phenology and thermal requirements of “Niágara Rosada” and “Niágara Branca” in the region of Laranjeiras do Sul, Paraná, Brazil (Revista de Ciências Agroveterinárias, 2018)
Grapevines are cultivated in several regions of Brazil, however, there is a lack of scientific information about the crop in the state of Paraná, especially in the region of Laranjeiras do Sul. The study of phenology is important because it allows the verification of variations of the answers that plants can give according to climatic changes of the environment where they are inserted. In addition, producers can program crop management from the record of the duration of phenological stages. Therefore, the objective of this study was to register the phenology and thermal requirements of the cultivars “Niágara Rosada” and “Niágara Branca” in the region of Laranjeiras do Sul, Paraná. The experiment was conducted on a family-owned property in Laranjeiras do Sul. The evaluations were carried out every two days, from pruning. Five phenological stages were evaluated: green tip; full bloom (50% of open flowers); “pea”-sized grains; start of cluster compaction and full maturation. A completely randomized block design with 10 replicates was used. The sample unit consisted of 20 plants, totaling 10 plants per cultivar. Analysis of variance was made using the F test, and when the treatment effects were significant the means were compared by Tukey’s test (p≤0.05). For “Niágara Branca”, a 124 days cycle was recorded and 1273.159 thermal accumulation in degree-days; for “Niágara Rosada”, 132.1 days and 1425 degree-days were registered. The cycle and the accumulation of degree-days of the cultivar “Niagara Rosada” was superior when compared to “Niágara Branca”, having influence on the management to be done over the cultivation period.
Keywords: Vitis labrusca L.; degrees day; climate